PENGARUH ASOSIASI MEREK TERHADAP KEPUTUSAN PEMBELIAN - Coriza Mayasari (Universitas muhammadiyah malang, 2014)
This research intent to determine the effect of Brand Associations which consists of Intangible Attributes, Benefits to Customers and Relative Prices significant influence the purchase decision and to determine variable dominant Brand Associations on purchasing decisions. This research, data were collected through a questionnaire technique on 100 respondents facial milk cleanser brand in Indomaret Viva by using Judgmental Sampilng techniques. Then performed an analysis of the data obtained through the test instrument using validity test and reliability test. The data analysis technique used is multiple linear regression analysis. Testing instrument through simultaneous test (F test) and partial test (t test) data processed resulting equation. Hypothesis testing using test through the coefficient of determination (R2), it is known that the Adjusted R2 indicates that the appropriate regression equation to predict the dependent variable, while the rest is explained by other variables that are not addressed in this study. F test results can be seen all over the independent variables consisting of Intangible Attributes, Benefits for Customers, and the relative price has a significant influence together (simultaneously) to the buying decision. Then the t test showed that the Customer Benefits shown to have a dominant influence on the dependent variable (purchasing decisions).Keyword: Intangible Attributes, Benefits to Customers, Relative Prices, Purchase Decision